Associations between change of direction, balance, speed, and muscle power in prepubescent soccer players - Hammami, R.; Granacher, U.; Pizzolato, F.; Chaouachi, M.; Chtara, M.; Behm, D. G.; Chaouachi, A. (Journal of Athletic Enhancement, 2017)
Relationships between change of direction (CoD), balance, speed, and power are less extensively studied in youth but provide important information for training. The aim of this study was to determine associations between CoD, balance, speed, and leg power in prepubescent soccer players. Thirty young male soccer players (9.26 ± 0.76 years; Peak-Height-Velocity: -3.42 ± 0.47 years) were assessed for CoD (shuttle run), Y-balance, speed (10-30-m sprint), and muscle power (unilateral, bilateral countermovement jumps [CMJ], unilateral, bilateral standing long jumps [SLJ], and triple hop test). Positive correlations were observed between the shuttle run, and 10-m (r=0.46) and 30-m sprint time (r= 0.47). Negative correlations were found between the shuttle run and SLJ (r=-0.44), bilateral CMJ (r= -0.42), and composite Y-balance (r=-0.49). Linear stepwise regression analysis revealed that 25% of the adjusted variance in the shuttle run test was explained by the Y-balance test (F=9.28; p<0.005). When the 10-m sprint test was added, explained variance amounted to 47% (F=11.87; p<0.001). Medium-sized associations were illustrated between speed, dynamic balance, and CoD in prepubescent soccer players. A greater emphasis on balance and sprint training might be an advantage for youth with less developed neuromuscular capabilities to improve CoD abilities.